2011
DOI: 10.1007/s00436-011-2666-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metarhizium anisopliae conidia mixed with soil against the eggs of Aedes aegypti

Abstract: The effectiveness of Metarhizium anisopliae IP 46 conidia mixed with soil was tested against Aedes aegypti eggs. Mycelium and new conidia developed first on eggs between 4.8 and 15 days respectively after incubation of fungus-treated soils at 3.3 × 10(3) up to 3.3 × 10(5) conidia/g soil at 25°C and relative humidities close to saturation. After 15-day incubation, 53.3% of the eggs exposed to soil with 3.3 × 10(5) conidia/g showed external development of mycelium and conidia. Fungus-inoculated soils (but not un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 14 publications
0
26
1
3
Order By: Relevance
“…In recent tests, the eclosion of A. aegypti larvae was also stimulated when eggs were exposed to soil mixed with water‐suspended IP 46 conidia (Leles et al . ). In multichoice tests offering water, moist filter paper or mud, gravid A. aegypti females strongly preferred to oviposit on mud (L.S.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In recent tests, the eclosion of A. aegypti larvae was also stimulated when eggs were exposed to soil mixed with water‐suspended IP 46 conidia (Leles et al . ). In multichoice tests offering water, moist filter paper or mud, gravid A. aegypti females strongly preferred to oviposit on mud (L.S.…”
Section: Resultsmentioning
confidence: 97%
“…, ; Leles et al . ). The broad insecticidal effect of M. anisopliae against both aquatic and terrestrial mosquito stages enhances the interest in this fungus for integrated control of culicid vectors as a means to diminish their transmission of diseases affecting humans and livestock.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another important point that deserves to be discussed is the concentration of conidia used in the in vitro control of A. aegypti. Most papers mention that concentrations may vary 10 6 -10 8 conidia/mL (Leles et al, 2011;Santos et al, 2009;Scholte et al, 2007). However, these studies focus on the use of entomopathogenic fungi.…”
Section: Resultsmentioning
confidence: 99%
“…Entomopathogenic fungi as antagonists of insect eggs with medical importance only recently gained more interest, especially against mosquito eggs (Luz et al 2007Santos et al 2009;Leles et al 2012;Sousa et al 2013). When it comes to triatomine targets, the only published study confirmed ovicidal activity by B. bassiana in R. prolixus (Romaña and Fargues 1992).…”
Section: Introductionmentioning
confidence: 99%